Attenuation of reflected waves in man during retrograde propagation from femoral artery to proximal aorta. (1st January 2016) - John Baksi, A.; Davies, Justin E.; Hadjiloizou, Nearchos; Baruah, Resham; Unsworth, Beth; Foale, Rodney A.; Korolkova, Olga; Siggers, Jennifer H.; Francis, Darrel P.; Mayet, Jamil; Parker, Kim H.; Hughes, Alun D.
Abstract: Background: Wave reflection may be an important influence on blood pressure, but the extent to which reflections undergo attenuation during retrograde propagation has not been studied. We quantified retrograde transmission of a reflected wave created by occlusion of the left femoral artery in man. Methods: 20 subjects (age 31–83 years; 14 male) underwent invasive measurement of pressure and flow velocity with a sensor-tipped intra-arterial wire at multiple locations distal to the proximal aorta before, during and following occlusion of the left femoral artery by thigh cuff inflation. A numerical model of the circulation was also used to predict reflected wave transmission. Wave reflection was measured as the ratio of backward to forward wave energy (WRI) and the ratio of peak backward to forward pressure (Pb /Pf ). Results: Cuff inflation caused a marked reflection which was largest at 5–10 cm from the cuff (change (Δ) in WRI = 0.50 (95% CI 0.38, 0.62); p < 0.001, ΔPb /Pf  = 0.23 (0.18–0.29); p < 0.001). The magnitude of the cuff-induced reflection decreased progressively at more proximal locations and was barely discernible at sites > 40 cm from the cuff including in the proximal aorta. Numerical modelling gave similar predictions to those observed experimentally. Conclusions: Reflections due to femoral artery occlusion are markedly attenuated by the time they reach the proximal aorta. This is due to impedance mismatches of bifurcations traversed in the backward direction. This degree of attenuation is inconsistent with the idea of a large discrete reflected wave arising from the lower limb and propagating back into the aorta.